Digital line guard / Kamarul Hamidi A Rahman - A Rahman, Kamarul Hamidi (1998)
The digital line guard is an electronic device designed to protect the telephone lines against bugging, wire-tapping and fraud. This product will fiilly paralyse and deactivate all those phenomena mentioned above. It is fiilly automatic, small in size, easy to connect and use. The advantages of this device are its free maintenance and no battery is required since the unit is fed by the protected line. This device is compatible with all telephone systems in all countries. The US type RG-ll socket system is used ie. the snap-in plug / socket installation. This project concentrates on the development of electronic circuit that can overcome problems such as protection firom fraud, saving on telephone bills and detection of broken lines.